The Study Analysis of Car Rim Design and Mechanical Properties Using Catia - Bayu Pranoto; Gunawan Chandra; Fakhruddin Muhammad; Trifiananto Muhammad; Purwanto (University of Muhammadiyah Malang, 2022)
This study discusses the design of a car rim and analyzed its mechanical properties using three different basic materials: aluminum, steel, titanium. The purpose of this study is to reduce production time and to minimize the risk of design failure. In this study using the Catia software to design a rim, then simulate the effect of applying force on a component, applying a certain working pressure, then able to perform calculations and display the results for analysis. The analytical method used is the FEM method of static analysis. The mesh type uses a linear tetrahedron mesh. Provision of clamps or fixed constraints is carried out on the surface of the bolt hole, where this surface is in contact with the wheel holder of car drive system. Then given a circumferential loading of 200 kN/m2. It was found that aluminum material is the best for the manufacture of car rims, which has a low density so it is lighter than steel and titanium. However, alloys such as lead and magnesium are needed to increase their hardness, and chromium alloys are needed to protect the rims from corrosion due to use in a polluted environment and contain impurities that can trigger corrosion.